An analysis of selected health behaviours of women as breast cancer risk factors - Kachaniuk, Hanna; Stanisławek, Andrzej; Bartoszek, Agnieszka; Kocka, Katarzyna; Szadowska-Szlachetka, Zdzisława; Charzyńska-Gula, Marianna (Menopause Review/Przegląd Menopauzalny, 2013)
Introduction : Health behaviours are the most important factor conditioning human health in approx. 50%. Also in cancer prevention the behaviours which women can have impact an on are crucial. Aim of the study : An attempt to diagnose selected health behaviours as breast cancer risk factors and to determine their scale using the Health Behaviour Inventory. Material and methods : The survey was carried out among 566 women from the Lubelskie Voivodeship in a period from March to November 2007. 37.5% of the surveyed were patients of 4 Lublin hospitals (group 1), while 62.5% accounted for healthy women, selected at random (group 2). To diagnose and assess health behaviours’ scale, a standardised research tool – the Health Behaviour Inventory, and the questionnaire were applied. Differences in the groups were significant when p ≤ 0.05. Results: The survey shows that overweight and obesity, alcohol abuse and low physical activity at work were significantly more frequent in women with cancer than in healthy women. No statistically significant differences were identified in consuming cereal products, fruit and vegetables, vegetable oils, fish, poultry, red meat and legumes. Passive forms of leisure were the most popular free-time activities. Women with cancer presented the declared health behaviours at a larger scale, including preventive behaviours and a positive mental attitude. Conclusions : The following breast cancer risk factors were found: overweight and obesity, alcohol abuse and low physical activity at work. A larger scale of declared health behaviours considerably more often concerned women after mastectomy than healthy women.